Addressing Challenges and Outcomes in the Biogas Sector: An Analysis of Efficiency, Economic Savings, and Environmental Impacts Using an Advanced SWOT Model - Luca Esposito; Chiara Vecchio; Giancarlo Cattaneo; Zhouyi Gu; Ester Scotto di Perta (Energies, 2023)
This study, through the use of company data, offers an in-depth analysis of the current situation and future prospects of biogas plants and how they can promote economic advantages and environmental benefits. The geographical context of the Piana del Sele (Salerno, Italy) was chosen on the basis of objective criteria, including its relevance in the agro-industrial sector and the availability of accurate and reliable company data that was collected through IT systems, including software business performance monitoring and digital data analysis. This choice was fundamental to guaranteeing the validity and representativeness of our analyses and results. From a methodological point of view, mathematical formulas and algorithms were used, which allowed the calculation of the biogas producibility indices by type of biomass as well as the quantification of the effluents produced to then estimate the quantification of the biogas and the interconnected economic savings. Furthermore, this study uses the SWOT (strengths, weaknesses, opportunities, and threats) approach in an innovative way by integrating renewable energy communities into it. The aim is to demonstrate the potential of biogas plants and how energy communities can transform weaknesses and threats into opportunities. The results show that the integration of biogas plants into the farm environment offers considerable potential, and although it is a challenge for small and medium-sized farms, it could bring energy self-sufficiency and economic surplus. Furthermore, the integration of renewable energy communities would be able to promote the diversification of energy supply and transform weaknesses and threats into opportunities.